2020
DOI: 10.3390/ijms21207741
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Mediated Long Non-Coding RNA Response in Macrophages in the Context of HIV

Abstract: Interferons play a critical role in the innate immune response against a variety of pathogens, such as HIV-1. Recent studies have shown that long non-coding genes are part of a reciprocal feedforward/feedback relationship with interferon expression. They presumably contribute to the cell type specificity of the interferon response, such as the phenotypic and functional transition of macrophages throughout the immune response. However, no comprehensive understanding exists today about the IFN–lncRNA interplay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In our analysis, it was observed that several deregulated lncRNA, as well as many PCG, could be regulated by IFN treatments. Expressions of several lncRNAs are shown to be modulated by treatment with IFNs [8,130,131]. Some of the deregulated lncRNA and PCG thus could be regulated in response to abnormal IFN in COVID-19.…”
Section: Involvement Of Deregulated Lncrna In the Pathogenesis Of Cov...mentioning
confidence: 99%
“…In our analysis, it was observed that several deregulated lncRNA, as well as many PCG, could be regulated by IFN treatments. Expressions of several lncRNAs are shown to be modulated by treatment with IFNs [8,130,131]. Some of the deregulated lncRNA and PCG thus could be regulated in response to abnormal IFN in COVID-19.…”
Section: Involvement Of Deregulated Lncrna In the Pathogenesis Of Cov...mentioning
confidence: 99%
“…Expression of lncRNA EGOT, NEAT1, BISPR/LncBST2, LINC01191/VIN/lnc-ACTR3, ISR (IFN-stimulated lncRNA) 2 and ISR8, LOC100506319/LINC01988/LncRNA-PAAN, LOC102637961/lncRNA-ACOD1, MIR155HG, TSPOAP1-AS1, PSMB8-AS1, PSORS1C3, IVRPIE was increased and expression of NRAV/DYNLL1AS1 was decreased in IAV infected cells 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 . In HIV infected cells expression of ISR2, NEAT1, GOMAFU/MIAT, LUST/RBM5-AS1, BIC/MIR155HG, MALAT1, NRIR/lncCMPK2, MIR3945HG, FIRRE, LINC02574, LINC01426 is increased while expression of NRON, PANDAR/PANDA, CDKN2B-AS1/ANRIL DD3/PCA, DANCR, CMPD/LINC01152, NCRMS/RMST, GAS5, LINC00173, lincRNA-p21/TP53COR1 and SAF/FAS-AS1 is decreased 29 , 30 , 31 . Increased expression of NEAT1, MAMDC2-AS1, PRINS, ISR2 and LOC102637961/lncRNA-ACOD1 is observed in HSV infected cells 24 , 27 , 32 , 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, with the introduction of large sequencing projects and a multitude of functional studies, lncRNAs have been recognized as key players in regulatory pathways and diseases, including HIV-1 infection [ 4 , 5 , 6 , 20 ]. Although ample in vitro research has led to substantial progress in understanding the role of lncRNAs during HIV-1 infection, little is known about their expression in vivo.…”
Section: Discussionmentioning
confidence: 99%